Applying the Ummi Method in Qur’anic Education at Patra Dharma 1 Primary School, Balikpapan - Zahro, Fatimatuz; Yusuf, Iskandar (Journal of Educational Research and Practice, 2024)
This research evaluates the implementation of the Ummi Method in Quranic education at SD Patra Dharma 1 Balikpapan. The results of interviews with Quranic teachers indicate that the Ummi Method brings a significant improvement in the learning process. Students show progress in reciting the Quran with proper tajweed and correction of errors. This method provides tangible benefits for students memorizing the Quran, facilitating their fluency in reading. The application of the Ummi Method at SD Patra Dharma 1 Balikpapan aligns with expectations, following training provided by the Ummi Surabaya team. SD Patra Dharma 1 Balikpapan is recognized as a model institution by the Ummi Foundation for Quranic education using the Ummi Method in Balikpapan. The results indicate an enhancement in Quranic recitation, with students learning through the Ummi Method positively influencing their classmates. The Ummi Method encompasses three approaches, one of which is the direct method, where students read without extensive explanations.